Diplomasi Budaya Amerika Serikat Melalui Musik Pop Di Indonesia (Studi Kasus Fenomena Michael Jackson Di Indonesia) - Farah Praweswari Novitasafitri; Anna Yulia Hartati (Faculty of Social and Political Sciences - Universitas Wahid Hasyim, 2021)
Cultural diplomacy is one of the diplomacy that has a long span of time in its application. Cultural diplomacy through pop music is one way that can be used by the United States in introducing their culture to Indonesia. The purpose of this study is to describe how the United States Cultural Diplomacy Through Pop Music in Indonesia (Case study: Michael Jackson phenomenon in Indonesia). Cultural diplomacy is not only through Michael Jackson's pop music, but also diplomacy through Michael Jackson's fan club to diplomacy through the mass media. This study used qualitative research methods. Where the data sources are obtained from books, news, and previous reports. The result is that cultural diplomacy through the music industry, especially pop music, can create a two-way connection between Indonesia and America, the people of each country also know their respective cultures and cultural diplomacy through the music industry has a long range of operations. Diplomacy through Michael Jackson's fan club also has a big influence on cultural diplomacy because through this fan club social and cultural interactions emerge from each fan. Diplomacy through the mass media is equally important because the mass media plays a major role in reporting Michael Jackson's music.